Penerapan Metode Holt-Winters untuk Forecasting Kebutuhan Gas Alam pada Perusahaan Listrik - Anjali, Nabila Putri; Tirkaamiana, Dean (Jurnal Teknik Industri Terintegrasi (JUTIN), 2026)
Accurate natural gas demand planning is a critical factor in maintaining the operational reliability of electricity companies. Discrepancies between planned and actual gas consumption, caused by fluctuations in generation load and dispatch decisions by P2B (Load Dispatch Center), highlight the need for an appropriate forecasting method. This study aims to forecast natural gas demand using the Holt–Winters Additive method based on historical gas consumption data from November 2023 to October 2025. The research adopts a quantitative approach with time series analysis and is processed using Minitab software. Model accuracy is evaluated using the Mean Absolute Percentage Error (MAPE) indicator. The results show that the optimal parameters α = 0.2, β = 0.6, and γ = 0 produce a MAPE value of 5%, which is classified as very good. The forecasting results can serve as a basis for more efficient gas supply planning and support the reliability of power plant operations.